Ammonia production by intestinal bacteria. Issue 3 (March 1973) - Vince, Angela; Dawson, A. M.; Park, N.; O'Grady, F.
Abstract : Bacterial growth and the production of ammonia from urea and by deamination of peptone has been examined at various pHs in both conventional static bacterial cultures and in a continuous cultivation system. Growth occurred on primary testing of 93 out of 100 strains of aerobic Gram-negative bacteria at pH 5, and 48 out of 50 strains of Esch. coli at pH 4·6. Hydrolysis of urea by Proteus mirabilis decreased steadily from pH 7·2 to pH 5·3; below pH 5·3 little hydrolysis occurred. Ammonia production from peptones by Esch. coli decreased from pH 7·2 to pH 4·6. Considerable variation was noted in the ability of different strains to produce ammonia. Experiments with cultures containing both Esch. coli and Pr. mirabilis showed that more ammonia was produced at low pH than was produced by cultures of single organisms. At low pH reduction in the count of organisms was not found to be an essential prerequisite for reduction of ammonia formation.